BIOSYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM MANGROVE BARK – RHIZOPHORA MUCRONATA EXTRACT - AT, AJI JOVITHA; B, DEIVASIGAMANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study attempted to synthesize AgNPs from mangrove bark Rhizophora mucronata and analyze characteristics. The synthesized AgNPs analyzed with UV–vis spectroscopy, high-resolution transmission electron microscopy (HRTEM), and energy-dispersive X-ray (EDX) for confirming the nanoparticles. Methods: The dried R. mucronata bark was powdered and kept in at 55°C for 15 min in a water bath and cooled at room temperature to get the extract. The R. mucronata bark extract was treated with silver nitrate and kept overnight in the dark environment which will turn the solution to dark brown color. The silver nanoparticles were characterized using UV–visible absorption at room temperature. Further characterization was also done with X-ray diffraction, high-resolution transmission electron microscope measurements, and DLS analysis. Results: The synthesized AgNPs were analyzed with various analytical methods that revealed the abundant presence of silver nanoparticles. The UV–vis spectroscopy analysis exposed the surface plasmon resonance peak of 422 nm. High-resolution transmission electron microscopy (HRTEM) analysis indicated the size ranging from 10 nm to 200 nm in diameter and a spherical shaped poly dispersal of the particles. The energy-dispersive X-ray (EDX) and DLS also confirmed the presence of silver atoms. Conclusion: Silver nanoparticles of Rhizophora mucronata bark revealed a well-defined structure and may be used in antimicrobial function in further researches.